Robotic approach to large tailgut cyst with malignant transformation: A case report. (2020) - Marano, Alessandra; Giuffrida, Maria Carmela; Peluso, Chiara; Testa, Valentina; Bosio, Paolo; Borghi, Felice
Abstract: Introduction: Tailgut cysts (TGC) are rare congenital retrorectal lesions deriving from vestiges of the hindgut. The risk of malignant transformation is relatively high. Thus early diagnosis and a complete removal of the mass are of paramount importance. We present a case of successful robotic exeresis of a large TGC adenocarcinoma. Presentation of case: A healthy 35-year-old woman was found to have a retrorectal TGC with suspected malignant transformation. The patient underwent complete robotic resection of the mass and pathology confirmed a TGC adenocarcinoma. The patient's post-operative course was unremarkable. At 24 months, the patient has not experienced any recurrence nor complained functional disorders. Discussion: The current case highlights the importance of TGC as a differential diagnosis of presacral masses, underscoring that malignant transformation can occur and may result in mortality and morbidity if radical surgery is not performed. Diagnosing TGC adenocarcinoma can be challenging because of its relatively low incidence. Biopsy is not recommended while magnetic resonance imaging (MRI) is indispensable in the evaluation of this lesion as the presence of intracystic vegetations could indicate a malignant transformation. Surgery is the mainstay of treatment and minimally invasive techniques have the potential to minimize morbidity and enhance recovery. Amongst these, the robotic approach can make the dissection of large lesions easier, reducing their manipulation and preventing nerve injuries. Conclusion: Robot-assisted resection of a TGC adenocarcinoma is safe and feasible. This approach can be particularly useful in the pelvis providing acceptable functional and oncological outcomes.